2019
DOI: 10.1016/j.nicl.2019.101843
|View full text |Cite
|
Sign up to set email alerts
|

Predicting conversion from mild cognitive impairment to Alzheimer's disease using brain 1H-MRS and volumetric changes: A two- year retrospective follow-up study

Abstract: This study investigated the ability of magnetic resonance spectroscopy ( 1 H-MRS) of posterior cingulate cortex (PCC) and brain volumetry to predict the progression from mild cognitive impairment (MCI) to Alzheimer's Disease (AD) on the basis of clinical classification at 2 years follow-up. Thirty-eight MCI patients, eighteen healthy older adults and twenty-three AD patients were included in this study. All participants underwent a brain-MR protocol (1.5 T GE scanner) including high-reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 39 publications
7
43
0
Order By: Relevance
“…This is a particular challenge, as mild cognitive complaints caused by incipient dementia are difficult to distinguish from non-pathological ageing processes (4). Previous studies indicate that metabolic changes can be detected in preclinical (29,37,49) and MCI stages (27,38). However, in order to assess the potential use of MRS for early detection, large-scale, preferably longitudinal studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a particular challenge, as mild cognitive complaints caused by incipient dementia are difficult to distinguish from non-pathological ageing processes (4). Previous studies indicate that metabolic changes can be detected in preclinical (29,37,49) and MCI stages (27,38). However, in order to assess the potential use of MRS for early detection, large-scale, preferably longitudinal studies are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…It is also worth taking a look at recent studies in which the clinical outcome was determined in a prospective study design, with three studies involving patients with MCI (27,30,35) and 283.0 T2,000/68 Singe-voxel AD (n=17),MCI (n=21),HC (N=15) 291.5 T2,000/25 Single-voxel Baseline: 303.0 T1,500/35 Single-voxel aMCI (n=48) + clinical follow-up after 3 years: AD (n=15), aMCI (n=33) one study involving cognitively healthy elderly individuals (29). The PCC was investigated in all studies.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The conversion rate from MCI to AD ranges from 23% to 68% for follow-up periods from 13 to 60 months. 7,9,[12][13][14][15][16] Dementia incidence in people over age 50 years with MCI is much higher than that in psychiatric outpatients of a similar age (249 vs 31 cases per 1000 person-years). 26 However, MCI has various pathologies, and not all MCI patients progress to dementia.…”
Section: Discussionmentioning
confidence: 97%
“…Neuroimaging studies have shown the brain regions associated with conversion from MCI to AD. Structural magnetic resonance imaging (MRI) has detected the temporal lobe, 7,9 medial temporal lobe, 7,10,11 hippocampus, 7,[12][13][14][15] and parahippocampal gyrus 16 as predictors of conversion, while functional neuroimaging has implied that the precuneus, 9,14 frontal cortex, 9 and temporoparietal cortex 15 are involved in conversion.…”
mentioning
confidence: 99%
“…In [ 16 ], these regions are included in the list of the ten anatomical regions with the largest entropy differences between normal and AD subjects. Related work [ 31 , 32 , 33 , 34 , 35 , 36 , 44 ] has highlighted the asymmetries between right and left hemispheres of the hippocampus as one of the regions with more relevance (beside hippocampal subfields and entorhinal cortices), but they use a subset of MCI patients.…”
Section: Discussionmentioning
confidence: 99%